Whole genome uniparental isodisomy detected using single nucleotide polymorphism (SNP) microarray in molar pregnancy: a case report - Onyinye O. Okonkwo; Veronica Ortega; Sheila Kane; Galina Aldrete; Paulina Ramirez; Philip T. Valente; Gopalrao V.N. Velagaleti (Molecular Cytogenetics, 2025)
Abstract Background Gestational trophoblastic neoplasms consist of complete and partial hydatidiform moles, both of which are considered aberrant conceptuses. Both conditions, complete hydatidiform mole (CHM) and partial hydatidiform mole (PHM), differ in histological characteristics, genetic origin and content and clinical features. CHM have a diploid karyotype, mostly 46,XX but lack maternal genetic contribution with all chromosomes of paternal origin. High-resolution SNP microarray testing is an efficient method used to determine the parental contribution of the genomic material in molar pregnancies and confirm the diagnosis. Case presentation We present a case of CHM in a 43-year-old, G3P2Ab1 who presented to the emergency department with 2 episodes of heavy bleeding. Chromosome analysis showed a normal 46,XX karyotype but with a homozygous pericentric inversion on chromosome 9. High-resolution SNP microarray studies detected whole genome uniparental isodisomy. Conclusion We present a case of CHM with homozygous pericentric inversion on chromosome 9 and whole genome uniparental isodisomy. This case illustrates the efficacy of high-resolution SNP microarray in confirming the diagnosis of CHM.